Perancangan Sistem Informasi Pengaduan Masyarakat Berbasis Web Menggunakan Metode Kanban pada Instansi Kepolisian - Adinda Nurul Hikmah Alkautsar; Anggita Anggita; Hana Alfiana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The public complaint system is an important facility for the police institution to improve the quality of public services, particularly in receiving, processing, and following up on various reports and complaints from the public. However, in practice, the complaint process is still largely carried out manually, such as through face-to-face interactions, paper-based forms, or direct communication that is not well documented. This gives rise to problems such as delays in handling, difficulties in tracking the history and status of reports, low work efficiency of officers, and limited transparency of information for reporters. These problems ultimately affect the level of public trust in the police institution. This study aims to design a web-based public complaint information system that supports a more structured, measurable, and transparent complaint management process. This system is designed by implementing the Kanban method as a workflow management tool that allows for prioritization, monitoring the handling process, and tracking the status of complaints in real time. The research methods include a literature review related to information systems and the Kanban method, direct observation of the existing complaint process, interviews with stakeholders, system requirements analysis, modeling using UML (Use Case Diagram, Activity Diagram, Sequence Diagram), and database design using Entity Relationship Diagram (ERD). The results of this research resulted in the design of a web-based public complaints information system that can facilitate complaint data recording, report management and status updates, task assignments to officers, performance monitoring, and complaint status notification to the public.